Tindakan Berorientasi Nilai Agama Dalam Novel Ngrangsang Lintange Luku Karya Narko “Sodrun” Budiman: (Kajian Sosiologi Sastra: Tindakan Sosial Max Weber) - Bella Aprilia Nova Sari; Octo Dendy Andriyanto (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This research aims to describe the form of religious value-oriented actions in the novel Ngrangsang Lintange Luku by Narko "Sodrun" Budiman. The theory used in this research is a literary sociology approach with the help of sosial action theory according to Max Weber's perspective. This research is descriptive and is a type of qualitative research. The data source for this research is the novel Ngrangsang Lintange Luku by Narko "Sodrun" Budiman. The data collection technique used is using library research and note-taking techniques. The data analysis technique used is the descriptive analysis method. Based on the research results, three aspects of religious values ​​were found in the religious value-oriented novel depicted in the novel Ngrangsang Lintange Luku, including aspects of faith, worship and morals. The most dominant aspect in this research is the aspect of worship, which consists of five data quotations, including: praying consisting of two dhata quotations, prayer consisting of two data quotations, and maintaining friendship consisting of one data quotation. And the most dominating figure in this religious values-oriented action is Miko.